2013
DOI: 10.3329/fmcj.v7i2.13504
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Rupture - Experience of 30 Cases at Faridpur Medical College Hospital

Abstract: :Rupture uterus is a rare and often catastrophic condition. It is associated with a high incidence of fetal and maternal mortality and morbidity. Our objective in this study is to determine incidence, etiology, trend, management, maternal and fetal outcome of uterine rupture in Faridpur Medical College Hospital. This is a prospective cross-sectional study of patients with ruptured uterus from the period of January 2011 to December 2011 admitted at Faridpur Medical College Hospital. All the cases of ruptured ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 2 publications
(2 reference statements)
1
16
0
Order By: Relevance
“…A total of 15 women with unscarred uterus had rupture, of whom 14 women were trying to deliver at home with the help of traditional birth attendants. History of oxytocin induction was very common at 52.5 % [3,5,[7][8][9]. Oxytocics are easily available and often misused [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 15 women with unscarred uterus had rupture, of whom 14 women were trying to deliver at home with the help of traditional birth attendants. History of oxytocin induction was very common at 52.5 % [3,5,[7][8][9]. Oxytocics are easily available and often misused [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of ruptured uterus in the present study was 7.03/1000 deliveries (0.7% 12,13 Our hospital is a tertiary referral centre, with most of the cases being referred in an already moribund state. Studies conducted in developing countries also showed that in rural areas, low socioeconomic condition of the people and poor health facilities were the major contributing factor in determining the incidence of ruptured uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence is 0.3/1000 to 7/1000 deliveries in India (1) and the perinatal mortality is as high as 74 to 94%. (2) According to WHO, incidence is 5.35 per 10000 live births. 0.8% after previous lower segment caesarean section, (3) >5% after classical caesarean section.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%